Clinical features and risk factors of pancytopenia: a study in a tertiary care hospital - Rao, Kande V. Mallikarjuna; Rao, Kande V. Mallikarjuna (International Journal of Advances in Medicine, 2017)
Background: Pancytopenia is one of the important hematological disorders seen in regular clinical practice, which is characterized by the decrease in all the three cellular elements of peripheral blood i.e. red blood corpuscles, white blood cells as well as platelets. The prevalence and risk factors are different in different geographical areas and hence this study was undertaken to identify the prevalence of pancytopenia in our area and analyse the risk factors. Methods: 42 patients with pancytopenia, of all age groups and both the sexes were included in the study. A detailed demographic and clinical history was taken from the patients. All of them were subjected to thorough physical examination; blood tests were collected for hematological study. Bone marrow aspirate was also taken form these patients. Results: Out of 42 patients, 54.8% patients were males and 45.3% were females, with most of them below 40 years of age. The most major cause of pancytopenia was megaloblastic anaemia comprising of 38.1% of the cases, followed by aplastic anaemia with 26.2%. The other minor contributors were leukaemia, malaria, malignancy, septicemia among others. Pallor, dyspnoea, fever were the most common symptoms observed. Conclusions: The study shows that there is a great incidence of pancytopenia in younger and middle age group rather than in the elderly. Detailed hematological examination including bone marrow aspiration should be done in these patients to understand and diagnose this disease early so that proper intervention and management of these patients can be done.